Tau as a fluid biomarker of concussion and neurodegeneration - Hossain Iftakher; Blennow Kaj; Posti Jussi P; Zetterberg Henrik (Future Medicine, 2025)
Concussion is predominant among the vast number of traumatic brain injuries that occur worldwide. Difficulties in timely identification, whether concussion led to neuronal injury or not, diagnosis and the lack of prognostic tools for adequate management could lead this type of brain injury to progressive neurodegenerative diseases. Tau has been extensively studied in recent years, particularly in repetitive mild traumatic brain injuries and sports-related concussions. Tauopathies, the group of neurodegenerative diseases, have also been studied with advanced functional imaging. Nevertheless, neurodegenerative diseases, such as chronic traumatic encephalopathy, are still conclusively diagnosed at autopsy. Here, we discuss the diagnostic dilemma and the relationship between concussion and neurodegenerative diseases and review the literature on tau as a promising biomarker for concussion.